2017
DOI: 10.1155/2017/2982478
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Fungal Infection to Dental Patients

Abstract: Fungi can cause various diseases, and some pathogenic fungi have been detected in the water of dental equipment. This environment offers suitable conditions for fungal biofilms to emerge, which can facilitate mycological contamination. This study verified whether the water employed in the dental units of two dental clinics at the University of Franca was contaminated with fungi. This study also evaluated the ability of the detected fungi to form biofilms. The high-revving engine contained the largest average a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…Filamentous fungi can also be considered as biofilmforming organisms because they are well adapted to grow on both biotic and abiotic surfaces. The formation of biofilms (Damasceno et al, 2017), but we did not recorded any filamentous fungi in this study.…”
Section: Discussionmentioning
confidence: 77%
“…Filamentous fungi can also be considered as biofilmforming organisms because they are well adapted to grow on both biotic and abiotic surfaces. The formation of biofilms (Damasceno et al, 2017), but we did not recorded any filamentous fungi in this study.…”
Section: Discussionmentioning
confidence: 77%
“…In 2008, contamination of the waterlines with Pseudomonas was reported in 20 dental clinics in São Paulo, and 28 out of 40 samples of water syringes had HPC measurements between 200 and 2000 CFU/mL [24]. More recently, in 2017, another study from Brazil reported fungal contamination of DUWLs [25]. The presence of mycobacteria was not assessed in these studies from Brazil.…”
Section: General Microbiological Quality Of Water In the Duwlsmentioning
confidence: 99%
“…Very few studies in Latin America have assessed water quality in dental offices. In fact, after searching the PubMed database, we found only three publications in the English language, all from Brazil [23][24][25]. In a 2003 study, 14 of the 15 dental units from private dental clinics in São Paolo had HPC measurements of approximately 50,000 to 300,000,000 microorganisms per milliliter [23].…”
Section: General Microbiological Quality Of Water In the Duwlsmentioning
confidence: 99%
“…dan Cryptococcus sp. 8 Candida merupakan salah satu genus flora normal rongga mulut. Candida dikenal sebagai mikroorganisme oportunistik yang pada kondisi tertentu mampu menyebabkan infeksi dan kerusakan jaringan.…”
Section: Pendahuluanunclassified